Effects of different crop years and sowing date on maize yield - Sedlák, Gergő; Széles, Adrienn (Acta Agraria Debreceniensis, 2014)
We carried out the tests in the flood meadow soil formed on the alluvial cone of Nagykereki, Sebes-Körös belonging to the Bihar plane small region. The aim of the study was to analyse the effect of the different sowing date of maize on the yield trend based on a comprehensive study conducted for 6 years (2007–2012).The sowing date of maize hybrids is a factor that significantly influences yield, however, its effect is not significant in each crop year. In the years when the date of sowing has a modifying effect, the reliable yield level can be reached with optimal sowing date management (24 April).The advantage of early sowing (10 April) proved to be dominant in the year of 2012, the seeds were placed into the still wet soil therefore shooting was more balanced. Maize seeds sown at the time of optimal (24 April) and late (10 May) sowing dates were placed into the already dry soil, which deteriorated germination and the strength of early initial development that had an effect on the yield.